Pendugaan model pertumbuhan dan bentuk sebaran spasial populasi banteng (Bos sondaicus d'Alton) di taman nasional alas purwo jawa timur - Yanto Santosa; Gugum Gumilar Paturohman (Jurnal Ilmu Pertanian Indonesia, 2009)
Population of bulls in the world is decreasing to 80%. On Java and Bali, the habitat of the species has declined by about 20% and 30% respectively (IUCN 2003). In Java, especially in Alas Purwo National Park, the decreasing population of bulls is caused by hunting and degradation of habitat. The estimation of growth bulls population in APNP is increase. The size of population in the beginning is 588 individuals the rate of growth is 0.093 and carrying capacity of habitat is 4772 individuals. The population will reach the carrying capacity by the year of 2126. The pattern of spatial distribution of bulls in APNP based on analysis of chi-square test is grouped (l2hit>l220.025). The pattern of distribution in low-land forest and platation forest is randomized (l20.975£l2hit£l20.025), meanwhile it is grouped in coastal forest ecosystem. The pattern of distribution in each type of ecoystem is influenced by the factor of resources (feedings, water, and salty water) and predation factor.